Reforming local government funding in England: The issues and options - David Phillips (Institute for Fiscal Studies (IFS), 2024)
A new, up-to-date system for allocating funding between councils is vital, and reforms must align with the broader vision for local government.
Keywords: 330; Government finances and spending; Devolution; Government spending; Local government finance; Public finance; Public sector